2014
DOI: 10.1016/j.sjbs.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urea and certain NPK fertilizers on the cereal cyst nematode (Heterodera avenae) on wheat

Abstract: Two outdoor pot experiments were conducted in two consecutive years under outdoor conditions during the wheat growing season in Saudi Arabia to determine the effects of urea and certain compound fertilizers (NPK), compared to the effects of the nematicide fenamiphos on the cereal cyst nematode (CCN), Heterodera avenae, and wheat growth. The results showed that all of the treatments, except the fertilizer diammonium phosphate (DAP), reduced the number of nematode cysts/root system and increased (P ⩽ 0.05) the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In other studies, urea might be lethal for juvenile, immature and mature earthworm of Eisenia foetida , by the mechanism of skin infiltration [ 29 ] and also toxic for filarial vector mosquito, Culex pipiens [ 30 ]. Some investigators observed that inorganic fertilizer (N-P-K) had potential to suppress cereal cyst nematode, Heterodera avenae population [ 31 ] as well as root-knot nematode population [ 32 - 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, urea might be lethal for juvenile, immature and mature earthworm of Eisenia foetida , by the mechanism of skin infiltration [ 29 ] and also toxic for filarial vector mosquito, Culex pipiens [ 30 ]. Some investigators observed that inorganic fertilizer (N-P-K) had potential to suppress cereal cyst nematode, Heterodera avenae population [ 31 ] as well as root-knot nematode population [ 32 - 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Amendments with urea provide additional benefits in suppressing the M. incognita population, as shown in our study. Previous reports have shown that urea and ammonia-releasing fertilizers are effective in controlling plant-parasitic nematodes (Santana-Gomes et al, 2013, Seifi and Bide, 2013, Al-Hazmi and Dawabah, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…(Verma and Nandal, 2006) and urea (Al-Hazmi and Dawabah, 2014). However, the tested approaches showed differences in their relative control efficacy under our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that the diversity and density of soil nematodes can change depending on the fertilization type used in fields ( Liang et al, 2009 ; Diacono and Montemurro, 2010 ; Al-Hazimi and Dacbah, 2014 ; Hu et al, 2014 ). Nitrogen fertilization significantly enhances the contents of soil ammonium and nitrate nitrogen, which have the potential to negatively impact soil nematodes ( Zhao et al, 2014 ; Song et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, negative effects upon soil nematodes were observed when a high level of phosphate fertilizer was applied in forest soils ( Zhao et al, 2014 ). Specifically, adding urea or calcium superphosphate alone can significantly inhibit the abundance of CCN ( Yang et al, 2008 ; Al-Hazimi and Dacbah, 2014 ). Ammonium sulfate fertilizer was found to significantly limit the abundance of soil nematode communities ( Ikoyi et al, 2020 ), whereas potassium sulfate promoted the occurrence of CCN-associated disease in wheat plants ( Yang et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%